Total Synthesis of the Psammaplysins: Evolution of a Dipolar Cycloaddition Approach - Morrow, Andrew P.; Smith, Myles W. (Synlett, 2025)
The psammaplysins are a unique group of bromotyrosine-derived natural products isolated from the Psammaplysilla genus of marine sponges. Aside from the various biological activities they possess, synthetic chemists have been drawn to the family for decades due to the intriguing 5/7-spiroisoxazoline-oxepine core common to all members. Herein, we describe our synthetic approach towards the psammaplysin family in the context of this broader work. Our route centers upon the use of a carefully choreographed alkoxymethylenation/1,3-dipolar cycloaddition to construct the key spiroisoxazoline-oxepine ring system, followed by its functionalization and divergent coupling to access various family members. We also detail the development of the first asymmetric approach to this class of marine natural products.1 Introduction2 Initial Synthetic Approach and Challenges Encountered3 Total Synthesis of Psammaplysins A, M, O and Q and Ceratinamide A4 Development of an Asymmetric Solution to the Family5 Conclusions and Outlook
Keywords: kinetic resolution; dipolar cycloaddition; nitrile oxide; total synthesis; psammaplysin; alkaloids